Senior entrepreneurship in emerging markets: evidence from the global entrepreneurship monitor - Stoyanov, Dimitar Krasimirov (2021)
This paper identifies the reasons for the higher level of senior entrepreneurship in developing countries compared to developed countries. The study focuses mainly on the five biggest emerging markets – China, India, Brazil, Russia and Mexico. It uses data from the Global Entrepreneurship Monitor 2016/17, 2017/18, 2018/19, 2019/20 and interviews with local experts to test twenty possible determinants of senior entrepreneurship in developing countries from the existing literature. The study finds that there is a moderate to strong relationship between the level of senior entrepreneurship and three of the twenty factors. Entrepreneurial intentions is the most important factor for the level of senior entrepreneurship. The other two factors that are positively correlated with senior entrepreneurship activity are confidence in one’s skills and the median age of a nation. This study should be of interest to policy makers, financial institutions and investors. The main limitations of this study are that it generalizes a complex phenomenon across a set of heterogeneous countries and relies to a large extend on a correlational analysis that in theory does not prove the existence of causal relationship between the variables.